REVERSE SHOULDER ARTHROPLASTY. HISTORY AND DEVELOPMENT PROSPECTS - Korzh, Mykola; Makarov, Vasyl; Pidgaiska, Olga; Tankut, Оleksiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
In elderly patients with a low bone mineral density primary endoprosthesis shoulder joint is one of the methods of surgical treatment. Goal. Perform a historical review of the development of reverse shoulder arthroplasty (RSA) with analysis of biomechanical features of existing implants, their advantages and disadvantages to identify possible areas for further ways of improvement. Methods. Search for scientific information was performed in electronic databases PubMed, ScienceDirect, Google Scholar with a search depth of 30 years. There were selected 68 sources. Results. Unsatisfactory results after shoulder hemiarthroplasty caused in patients with severe damage to the rotator cuff and multifragmental fractures of the proximal humerus using RSA. Endoprosthesis design C. Neer replaced the implants of P. Grammont design, built on the principles: spherical glenoid component, concave support part on the humerus, the center of rotation at the level or medially of the scapular neck, proximal humerus fractures is displaced medially and distally. Medialization of the center of rotation is an unfavorable factor that leads to loss of tension of the deltoid muscle. To eliminate this disadvantages, lateralized hemispheres have been developed, with the help of which stability is achieved, the formation of a defect of the lower edge of the scapular neck is prevented. Their size affects on the volume of movements: the smallest diameters should be used for prevention of soft tissue strain. Note that the use of RSA with a lateralized center of rotation and varus shoulder component brings biomechanics closer shoulder joint to normal anatomical features. Conclusions. The main directions of RSA improvement: conducting biomechanical research to evaluate structures endoprostheses in order to choose the optimal design; introduction of modern additive technologies that will allow to obtain porous components with increased osteointegrative properties; reduce the weight of the hemisphere; improving friction pairs